A Scientific Approach of using the DMAIC Methodology to Investigate the Effect of Cutting Tool Life on Product Quality and Process Economics: A Case Study of a Saudi Manufacturing Plant - Aichouni, A. B. E.; Abdullah, H.; Ramlie, F. (Engineering, Technology & Applied Science Research, 2021)
One of the major priorities for manufacturing companies in the globalized economy is the ability to offer high-quality products to customers at the lowest production cost. Globally, process improvement methods and techniques are used to reduce waste and improve product and service quality. This paper aims to propose a systematic model based on process improvement methodologies and tools to help the manufacturing companies decide on cutting tool life and other manufacturing issues. This research seeks to prove that some common industry practices, such as changing cutting tools in machining processes, can significantly affect the economics of production and the overall performance of the plant. The research is mainly based on analyzing real field data using the DMAIC methodology to identify improvements in order to achieve a balance between economy and quality in a Saudi manufacturing plant. Although the study was concerned only with changing cutting tools in the machining process in an air conditioning plant, its findings and conclusions can be generalized to all manufacturing processes.